Islam Without a Veil : Kazakhstan's Path of Moderation - Salhani, Claude (Book collections on Project MUSE., 2011)
Examines the religious and political foundations of modern day Kazakhstan and argues that the country should serve as an example for other Muslim nations to live peacefully with citizens and international neighbors alike.